Evaluation and revision of long-range single-site lightning location accuracy considering the time delay of ground wave - Zhou, Jiahao; Zhang, Qilin; Zhang, Junchao; Dai, Bingzhe; Li, Jie; Wang, Yao; Gu, Jiaying (Frontiers in Environmental Science, 2023)
Detecting the distance and orientation of long-distance thunderstorms has very important practical significance. The multi-station lightning location system relies on a high-precision time module and good network communication capabilities, but in some cases these conditions cannot be met, but there is still a need for lightning activity monitoring, and it is very important to establish a single-site lightning location system. In this paper, we have established a long-distance single-site lightning location station, and in order to improve the accuracy of distance estimation, a numerical algorithm is used to obtain the relationship between the ground wave arrival time delay and the propagation distance, and it is used to revise the time difference between the peak value of the skywave and ground wave. Moreover, we used multi-station lightning location data to revise the site-error in magnetic direction finder method to improve the accuracy of the direction calculation. The results show that the effective detection range of the single-site we have been established is 200km-2000km, and the revised average direction deviation dropped from 12.3° to 8.6°. The verification results of thunderstorms within the effective detection range show that the relative error of single-site lightning location is 8.4%-18.6% after the revision.